Criterion-oriented Ethics, a Neglected Field of Study in Islamic Ethical Research - Muhammad Motahari Farimani (اخلاق وحیانی, 2012)
Research in the area of Islamic Ethics which is capable of having profound effects on individual behavior has not yet been surveyed carefully. We entitle this area of research ‘‘Criterion-Oriented Ethics’’, which in the history of our moral legacy has not been mentioned but some slight points. Criterion-oriented ethics is to provide one with their own record of practical ethics and identify some criteria to enable him to assess his soul. For example he can not only assess his soul on having high moral virtues such as honesty or not having spiritual vices such as envy, but also he will be informed of his general ethical status. Some of the Quranic verses and narrations have brought this perspective of ethical issues to human's notice. However the criterion-oriented ethics has not been considered as a separate field of study in ethics. This paper aims to express the status, features and challenges of research in the field of criterion-oriented ethics.